Genetic Signatures of Contrasted Outbreak Histories of “Candidatus Liberibacter asiaticus”, the Bacterium That Causes Citrus Huanglongbing, in Three Outermost Regions of the European Union - Olivier Pruvost; Karine Boyer; Frédéric Labbé; Marine Weishaar; Anaïs Vynisale; Claire Melot; Cécile Hoareau; Gilles Cellier; Virginie Ravigné (Evolutionary Applications)
ABSTRACT In an era of trade globalization and climate change, crop pathogens and pests are a genuine threat to food security. The detailed characterization of emerging pathogen populations is a prerequisite for managing invasive species pathways and designing sustainable disease control strategies. Huanglongbing is the disease that causes the most damage to citrus, a crop that ranks #1 worldwide in terms of fruit production. Huanglongbing can be caused by three species of the phloem‐limited alpha‐proteobacterium, “Candidatus Liberibacter,” which are transmitted by psyllids. Two of these bacteria are of highest concern, “Ca. Liberibacter asiaticus” and “Ca. Liberibacter africanus,” and have distinct thermal optima. These pathogens are unculturable, which complicates their high‐throughput genetic characterization. In the present study, we used several genotyping techniques and an extensive sample collection to characterize Ca. Liberibacter populations associated with the emergence of huanglongbing in three French outermost regions of the European Union (Guadeloupe, Martinique and Réunion). The outbreaks were primarily caused by “Ca. Liberibacter asiaticus,” as “Ca. Liberibacter africanus” was only found at a single location in Réunion. We emphasize the low diversity and high genetic relatedness between samples from Guadeloupe and Martinique, which suggests the putative movement of the pathogen between the two islands and/or the independent introduction of closely related strains. These samples were markedly different from the samples from Réunion, where the higher genetic diversity revealed by tandem‐repeat markers suggests that the disease was probably overlooked for years before being officially identified in 2015. We show that “Ca. Liberibacter asiaticus” occurs from sea level to an altitude of 950 m above sea level and lacks spatial structure. This suggests the pathogen's medium‐ to long‐distance movement. We also suggest that backyard trees acted as relays for disease spread. We discuss the implications of population biology data for surveillance and management of this threatful disease.